The Influence of the Four Pillars of Diabetes Mellitus Control on Complications in Diabetes Mellitus Patients - Diki Arif Hidayat; Dedi Supriadi; Endrian Mulyadi Justitia Waluyo; Andan Firmansyah; Iif Taufiq El Haque (Jurnal Vocational Nursing Sciences (VNUS), 2019)
There needs to be an effort in the management of Diabetes mellitus to keep blood sugar levels as close to normal as possible to prevent complications. Diabetes mellitus control can be done through four pillars, namely education, medical nutrition therapy, physical exercise, and pharmacological intervention. According to data from the District Health Office. Ciamis in 2019 there were 305 people suffering from diabetes mellitus in Kawali sub-district. The purpose of the study was to determine the effect of the four pillars of diabetes mellitus control on the incidence of complications in people with diabetes mellitus in Kawali sub-district, Ciamis district. This research is a descriptive-analytic study using a cross-sectional approach. Samples were taken using the purposive sampling method as many as 30 respondents. Data were collected using questionnaires and observation sheets. Data analysis used the Chi-Square test with a 95% confidence level. The results showed that 83% of respondents had a good level of education, 60% had appropriate medical nutrition therapy settings, 60% did not do physical exercise, and 66.7% adhered to pharmacological interventions. The results of statistical tests showed that there was a relationship between the pillars of education, medical nutrition therapy, and pharmacological intervention with the incidence of complications in people with diabetes mellitus in Kawali sub-district, Ciamis district. There is no relationship between physical exercise and the incidence of complications in people with diabetes mellitus in Kawali sub-district, Ciamis district